Willingness to Pay for Improvement in Service Quality of Intermediate Public Transport (IPT) Modes - Saurabh Kumar; Sanjeev Sinha (Salehan Institute of Higher Education, 2021)
The Rapid increase in urban population has put extraordinary pressure on transport infrastructure. Public transport frameworks in small and medium-sized cities in developing countries include of IPT modes. However, these midsized cities in developing countries face congestion problems and have severe environmental pollution. The paper focuses on the assessment of willingness to pay for improvement in service quality of IPT mode of transportation in urban India. A Stated Choice (SC) survey instrument was designed and data was collected from IPT users to collect respondent’s socio-economic characteristics and their attributes for the stated hypothetical scenarios. Respondents were approached randomly and face-to-face interviews were carried out. The present study aimed at finding the willingness to pay for different attributes of an IPT mode to assess the relative importance of these attributes. The multinomial logit model was developed using the econometric software NLOGIT 4.0. The results obtained from the analysis suggest that the commuters in the city perceive safety as the most important attribute of an IPT mode followed by comfort and waiting time. The findings of the study shall be useful for policy makers and operators in urban planning and improvement of the transportation systems of mid-sized cities of developing countries and any new mode incorporating high comfort and safety shall be preferred. Doi: 10.28991/cej-2021-03091696 Full Text: PDF